PELATIHAN PEMBUATAN SABUN MANDI CAIR LIDAH BUAYA SEBAGAI UPAYA KEMANDIRIAN WARGA BINAAN PANTI ASUHAN - Nursal, Fith Khaira; Amalia, Anisa; Nining, Nining; Sunaryo, Hadi (JURNAL PENGABDIAN FARMASI DAN SAINS, 2023)
The social problems of children with difficult economic environments or incomplete families are the concern of the government and society to overcome them. Al-Ma'un Orphanage is one of Muhammadiyah's charitable efforts as a social institution that provides religious guidance and other creativity for foster children so that they can be independent and useful for society. This orphanage fosters approximately 30 children of various ages. The aim of the foster child development system to created of independent creativity through training in making herbal liquid bath soap. Aloe vera is a plant that is easy to grow and has many benefits for skin health such as moisturizing, softening, and as an antioxidant that can inhibit the premature aging process of the skin. Training is carried out using educational and experimental methods by directly involving participants. The results of the training were measured through the evaluation of the pre-test and post-test values with significant results based on the statistical analysis of the paired t-test (p <0.05). There was a significant increase in participants' knowledge before and after the training activity. This training is not only aimed at nurturing, but also providing provisions for children so that one day they will have hope and a better future because children as God's mandate, the next generation of the nation must get the widest possible opportunity to grow and develop optimally.